Real Time Hybrid Detective Security System Using GSM Technology - Friday, Ebole Alpha (Journal of Science & Technology, 2021)
Security has become an important issue everywhere and it is becoming necessary nowadays as the possibilities of intrusion are increasing day by day. Safety from theft, ritual killing like badoo in Lagos state Nigeria, as well as October 20th demonstration that was hijack by hoodlum in Nigeria, leaking of raw gas, Human intrusion and fire disaster are the most important requirements of home security system for people. A traditional security system gives the signals in terms of alarm for notification. However, the GSM (Global System for Mobile communications) based security systems provides enhanced security as whenever a signal from sensor occurs from integrated fire alarm system, gas leakage system and human intrusion system, a text message is sent to a desired number(s) to take necessary actions. This research employs a method for Real time intrusion detective security system for fire, gas, and human intrusion, where signal is send through SMS with the application of GSM Technology (sim548c) in line with Atmega644p microcontroller, sensors, relays and buzzers.